Interrelation of magnetic susceptibility, soil color and elemental mobility in the Pliocene–Pleistocene Siwalik paleosol sequences of the NW Himalaya, India - Kumaravel, V.; Sangode, S.J.; Siddaiah, N. Siva; Kumar, Rohtash (My University, 2010)
Apart from imparting color characteristics, the precipitation and dissolution of Fe-oxides (and hydroxides) during pedogenesis is coeval with transformation and translocation of major and trace elements. Based on rock magnetic and geochemical parameters for 27 paleosol profiles from three stratigraphic columns of Pliocene–Pleistocene Siwalik sequence in the NW Himalaya, we describe here the relationship amongst elemental mobility, Munsell color and low field mass normalized magnetic susceptibility (χlf). The study shows a consistent positive correlation of the rock magnetic parameters (principally magnetic susceptibility) with Munsell hue and Redness Rating (RR) index (Torrent et al., 1980, Blavet et al., 2000) of the soil profiles. The Late Miocene profiles show an increase of ~ 29% of Al2O3 concentration and that for the Pliocene and Pleistocene profiles show ~ 33 to 60% increase as a result of pedogenesis. Similarly the other immobile elemental oxide, Fe2O3 is increased by ~ 54% in the Late Miocene profiles and ~ 50 to ~ 63% in the Pliocene–Pleistocene profiles. Geochemical trends correlate with the χlf, showing R2 = 0.39 to 0.68 with Al2O3 and Fe2O3 and R2 = − 0.40 to − 0.73 for SiO2. Similarly the Munsell color parameters, especially the RR index display significant positive correlation where the magnetic mineralogy is dominated by hematite and goethite. These first order relationships amongst χlf, RR index and elemental mobility demonstrate the potential use of magnetic susceptibility for rapid characterization of the widespread and heterogeneous pedogenic episodes within the dynamic sedimentary environments of the Himalayan foreland basin.
Keywords: Magnetic susceptibility; Elemental mobility; Soil color; Paleosols; Siwaliks; Himalayan Foreland Basin; NW Himalaya